Geochemistry and sedimentary photopigments as proxies to reconstruct past environmental changes in a subtropical reservoir - Cardoso-Silva, Sheila (2022)
Sediment cores were used to establish past environmental impacts associated with eutrophication, erosion and metal contamination in the subtropical Atibainha reservoir (São Paulo State, Brazil). We hypothesize that: (1) the levels of nutrients, determined by a spectrophotometric method, reflect the contributions of these elements over time and (2) changes in sedimentation rates, determined by 210Pb geochronology, and metal flows, determined by ICP-AEOS, are related to anthropic activities. Stratigraphic changes in the analysed variables were used to divide the sediment cores into three intervals, according to PCA and cluster analysis (Euclidian distances, Ward’s method). Interval I, composed by the period prior to operation of the reservoir, was influenced by organic matter levels. Interval II, between 1967 and 1993 (PC2: 14.94% of the total variability), a period of minor impacts, was mainly influenced by Mn (eigenvalue of 0.71) and Zn (0.74). Interval III, which included sediment deposited between 1993 and 2015 (PC1: 60.28% of the total variability), was influenced by the highest levels of the pigments lutein (0.86), zeaxanthin (0.90) and fucoxanthin (0.65), together with total nitrogen (0.78) and sedimentation rate (0.91), suggesting changes in the phytoplankton community composition probably associated to the intensification of eutrophication and erosion processes. Despite the limitations of applying paleolimnological techniques in reservoirs and the use of pigments as proxies in regions with higher temperatures, it was observed that the anoxic conditions and the aphotic environment in the hypolimnion acted to preserve pigments associated with the groups Chlorophyta (lutein), Cyanobacteria (zeaxanthin) and Bacillariophyta (fucoxanthin). The isolated analysis of nutrients was not sufficient to make conclusive inferences regarding the eutrophication history, since the levels of TP tended to decrease over time, in contrast to an increase in the levels of TN. Despite intensification of eutrophication and erosion, associated to anthropic activities, no signs of metal contamination were recorded.